ANALISIS KEBUTUHAN BAHAN AJAR ULUMUL QUR’AN - Isgandi, Yiyin; Darmawan, Achmad Anang (Sekolah Tinggi Ilmu Al-Quran dan Sains Al-Ishlah, 2024)
This study aims to determine students’ need about the form of teaching developed for learning the Ulumul Qur’an at Teacher Education College. The sample was randomly selected as many as 80 from 130 new students of higher aducation college. Data was collected using observation sheets for lecture activities, interview sheets and open questionnaires for students. The results of lecture observations show that students need a long time to find material from various sources, not yet focused on learning and lecturers are still the main source. Learning contraints because students do not have systematic teaching materials to make it easier to achieve learning objectives. The result of the analysis of interviews and questionnaries of student needs show that; 1) the most needed teaching materials are textbook; 2) the materials in the textbook includes how to integrate the values of the Qur’an in teaching and learning, the miracles of the Qur’an, the narration of the Qur’an, the relationship of verses and letters, Makkiyah and Madaniyah verses, the descent of the Qur’an, various qira’at, parables and oath verses, muhkam and mutashabih verses. This study is the initial part of the research and development of textbook Ulumul Qur’an at Teacher Education College.